A Highly Sensitive Fibrous Luminescent Probe Based on Anthracene Triarylamine for Nitroaromatic Explosives. Issue 11 (29th September 2022) - Zhao, Qiang; Xia, Yongrong; Xue, Wei; Song, Zhao; Lu, Wei; Jin, Dong; Xie, Linghai; Zhao, Jianfeng; Shi, Naien
Abstract: The rapid, sensitive, and efficient detection of nitroaromatic explosives (NAEs) is extremely important for human health and public safety; however, it is still a big challenge, especially for the detection of trace amounts of explosive vapors. In this study, a small‐molecule luminescent probe of an anthracene triarylamine derivative was synthesized and employed as a highly efficient and sensitive sensor for the detection of NAEs, including 2, 4‐dinitrotoluene (DNT), 4‐nitrotoluene (4‐NT), and nitrobenzene (NB). The fluorescence intensity varied linearly along with the concentration of NAEs in the diluted tetrahydrofuran solution. The K SV values (Stern‐Volmer equation coefficient) were 2457, 1735, and 1286 M −1 for DNT, 4‐NT, and NB, respectively (DNT>4‐NT>NB). Furthermore, polystyrene/LiCl/AnPh electrospun fibrous films were manufactured and proved to be efficient fluorescence sensors for NAEs vapor. This quenching can be ascribed to the photo‐induced electron transfer (PET) process between the AnPh probe and NAEs analytes. The large contact area between the nanofibers and analytes in the film also contributed to the efficient quenching effect. This work will stimulate the design of new fluorescent probes for electrospun fibrous NAEs sensors and pave the way for their applications in future practical fields of public safety control. Abstract : A highly sensitive fluorescent sensor based on polystyrene and N, N ‐diphenylanthracen‐2‐amine composite fibers for the detection of nitroaromatic explosives via electrospun technology was constructed. Furthermore, electrospun nanofiber films with better sensing performance were achieved by doping LiCl into an electrospun precursor solution. The resulting nanofiber films fabricated by electrospun technology exhibited the high detection performance.